Naturally occurring lesions of the uterine tube in sheep and serologic evidence of exposure to Chlamydophila abortus. - Tomlinson, L (2000)
The uterine tubes from 405 ewes, collected at an abattoir, were assessed grossly and microscopically for abnormalities that correlated with serological evidence of exposure to Chlamydophila abortus. Gross lesions were found in 41 ewes and 86 had microscopic lesions. Enzyme immunoassay (EIA) of serum was used as an indication of exposure of individual ewes to C. abortus; 52 were found to be positive. Chi-squared analysis indicated no association between EIA-positive animals and lesions of the uterine tube.